Perlakuan Celup Puting setelah Pemerahan terhadap Keberadaan Bakteri Patogen, Staphylococcus aureus, Streptococcus agalactiae, dan E. coli pada Sapi Perah Penderita Mastitis Subklinis di Peternakan KUNAK Bogor - Herwin Pisestyani; Etih Sudarnika; Rachmi Ramadhanita; Abdul Zahid Ilyas; Chaerul Basri; Ardilasunu Wicaksono; Arifin Budiman Nugraha; Mirnawati B Sudarwanto1 (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Mastitis is udder inflammation that can be caused by the entry of pathogenic bacteria through the teat. One of the treatments that can prevent bacteria infection is teat dipping. This research was aimed to identify the effectof teat dipping after milking to the presence of pathogenic bacteria that cause subclinical mastitis (Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli) and the presence of pathogenic bacteria that cause subclinicalmastitis by quarter of udder. Milk samples were taken from normal lactation period of dairy cows, clinically healthy, and positive subclinical mastitis status when the intervention was applied. Sixty seven samples of quarters from 18dairy cows were identified to the presence of pathogenic bacteria that cause subclinical mastitis before teat dipping and at 1st, 2nd, and 3rd months after teat dipping. Identification of the presence of pathogenic bacteria was done byculturing samples on selective agar media. The presence of common pathogenic bacteria, Staphylococcus aureus, and Escherichia coli decreased significantly after teat dipping, while Streptococcus agalactiae and other pathogenicbacteria did not decrease significantly. The presence of pathogenic bacteria based on the quarter of udder did not show the significance difference. Application of teat dipping after milking was able to decrease the presence ofpathogenic bacteria that cause subclinical mastitis.